XVI–XIX CENTURIES URBAN BAZAARS OF CENTRAL ASIA: CENTERS OF ECONOMIC AND SOCIAL LIFE - Saxobiddin Aslon o`g`li (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract.This article analyzes the urban bazaars of Central Asia in the 16th–19th centuries as centers of economic, social, and cultural life. During this period, the political structures of the Bukhara, Khiva, and Kokand khanates used urban markets as an important instrument in shaping their economic systems. The bazaars contributed not only to the development of domestic trade but also to the establishment of foreign trade relations. Through these markets, local handicraft products, foodstuffs, livestock, silk and atlas fabrics, carpets, and jewelry were sold in internal markets, while trade relations were conducted with Russia, Iran, India, and China.Bazaars were an integral part of urban infrastructure and were organized through various rows of shops (rastalars), trading domes (tims), caravanserais, and covered market structures. Trade processes were supervised by muhtasibs (market inspectors), and systems were developed to stabilize prices and ensure quality control.Urban bazaars also played a significant social and cultural role. Public gatherings were held there, announcements were made, craft guilds operated, and festivals and ceremonies were organized. Bazaars functioned not only as economic centers but also as hubs of cultural exchange, information dissemination, and social interaction. Through caravan routes, merchants arrived from distant regions, contributing to urban economies and the development of handicrafts.The article systematically examines the role of urban bazaars in the political and economic system, internal and external trade relations, craft centers, monetary circulation, and the social and cultural significance of markets. It also explores the processes of economic and cultural integration formed through urban bazaars during this period. The study contributes to a deeper understanding of the economic history of Central Asian cities and provides a scholarly basis for researching the region’s trade and craft systems.